Public budget on a university campus: the Analytic Hierarchy Process in aiding decision-making - Câmara, Kathiurcia Montovanelli Cazotti; Chiquieri, Julien; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
In the current Brazilian context, universities have experienced a rationalization of budgetary and financial resources, caused by cuts in the federal government’s budget. This limitation has made the management of these institutions more and more challenging, making their managers need to make effective and efficient decisions, aiming to ensure the best possible use of available resources. For this reason, this work aimed to assist in the definition of priorities for the contingency of available resources of a Northern University Center of Espírito Santo. For this, the Analytic Hierarchy Process (AHP) method was used. It was verified with the research that the managers are not satisfied with the retraction situation, but understand that it is necessary to look for ways to minimize the impacts caused by it. The results found suggest that the Teaching, Research and Extension factor for the current context of the research unit, is considered to be the most relevant, with the indication of the Purchase of Consumable and Permanent Materials as a high priority alternative. The approach adopted in this work presents itself as a possible tool to support decision making for public managers.